Communicating about sustainability on @greenpeaceid - Sirajuddin; GS, Achmad Daengs; Saragih, Megasari Gusandra; Surya, Elfitra Desy; Sandoval, Marcos R. B. (Jurnal Studi Komunikasi, 2022)
Environmental challenges are critical issues that the entire international community is currently dealing with. The number of incidents of factory waste disposal, climate change, and biodiversity extinction all represent a significant threat to all creatures' survival. As a result, Greenpeace, as an environmental group, continues to work to stop the ongoing natural damage. This study aims to find out the sustainable communication model on the Greenpeace social media site. From January 1, 2022, to February 28, 2022, Krippendorff content analysis via Instagram @greenpeaceid was used. Based on the data analysis that has been carried out, sustainability communication on the Instagram @greenpeaceid social media site for the period January 1, 2022, to February 28, 2022, is more dominant in producing posts that contain the benefits of messages that invite people to care about environmental balance.